Pathogenic and Virulence Factor Detection on Viable but Non-culturable Methicillin-Resistant Staphylococcus aureus - Jiang, Hua; Wang, Kan; Yan, Muxia; Ye, Qian; Lin, Xiaojing; Chen, Ling; Ye, Yanrui; Zhang, Li; Liu, Junyan; Huang, Tengyi (Frontiers in Microbiology, 2021)
Food safety and foodborne infections and diseases have been a leading hotspot in public health, and methicillin-resistant Staphylococcus aureus (MRSA) has been recently documented to be an important foodborne pathogen, in addition to its recognition to be a leading clinical pathogen for some decades. Standard identification for MRSA has been commonly performed in both clinical settings and food routine detection; however, most of such so-called “standards,” “guidelines,” or “gold standards” are incapable of detecting viable but non-culturable (VBNC) cells. In this study, two major types of staphylococcal food poisoning (SFP), staphylococcal enterotoxins A (sea) and staphylococcal enterotoxins B (seb), as well as the panton-valentine leucocidin (pvl) genes, were selected to develop a cross-priming amplification (CPA) method. Limit of detection (LOD) of CPA for sea, seb, and pvl was 75, 107.5, and 85 ng/μl, indicating that the analytical sensitivity of CPA is significantly higher than that of conventional PCR. In addition, a rapid VBNC cells detection method, designated as PMA-CPA, was developed and further applied. PMA-CPA showed significant advantages when compared with PCR assays, in terms of rapidity, sensitivity, specificity, and accuracy. Compared with conventional VBNC confirmation methods, the PMA-CPA showed 100% accordance, which had demonstrated that the PMA-CPA assays were capable of detecting different toxins in MRSA in VBNC state. In conclusion, three CPA assays were developed on three important toxins for MRSA, and in combination with PMA, the PMA-CPA assay was capable of detecting virulent gene expression in MRSA in the VBNC state. Also, the above assays were further applied to real samples. As concluded, the PMA-CPA assay developed in this study was capable of detecting MRSA toxins in the VBNC state, representing first time the detection of toxins in the VBNC state.